Nocturnal digital surveillance in aged populations and its effects on health, welfare and social care provision: a systematic review - Matt X. Richardson; Maria Ehn; Sara Landerdahl Stridsberg; Ken Redekop; Sarah Wamala-Andersson (BMC, 2021)
Abstract Background Nocturnal digital surveillance technologies are being widely implemented as interventions for remotely monitoring elderly populations, and often replace person-based surveillance. Such interventions are often placed in care institutions or in the home, and monitored by qualified personnel or relatives, enabling more rapid and/or frequent assessment of the individual's need for assistance than through on-location visits. This systematic review summarized the effects of these surveillance technologies on health, welfare and social care provision outcomes in populations ≥ 50 years, compared to standard care. Method Primary studies published 2005-2020 that assessed these technologies were identified in 11 databases of peer-reviewed literature and numerous grey literature sources. Initial screening, full-text screening, and citation searching steps yielded the studies included in the review. The Risk of Bias and ROBINS-I tools were used for quality assessment of the included studies. Result Five studies out of 744 identified records met inclusion criteria. Health-related outcomes (e.g. accidents, 2 studies) and social care outcomes (e.g. staff burden, 4 studies) did not differ between interventions and standard care. Quality of life and affect showed improvement (1 study each), as did economic outcomes (1 study). The quality of studies was low however, with all studies possessing a high to critical risk of bias. Conclusions We found little evidence for the benefit of nocturnal digital surveillance interventions as compared to standard care in several key outcomes. Higher quality intervention studies should be prioritized in future research to provide more reliable evidence.